English vocabulary in use : - McCarthy, Michael (Cambridge University Press, 1994)
English Vocabulary in Use is a vocabulary book for upper-intermediate and advanced learners of English, primarily designed as a self-study reference and practice book, but can also be used for classroom work. Firmly based on current learning theory, its emphasis is on the practical needs of the learner. It aims not only to present and explain words but to demonstrate how to use them and how to work out rules for using them. Vocabulary is explained and presented on left-hand pages with a wealth of innovative follow-up activities opposite. * 100 units, covering approximately 3,000 new vocabulary items * offers learners the opportunity to consolidate and expand existing vocabulary * promotes invaluable learning techniques * gives study tips and suggests follow-up tasks * contains a comprehensive key with additional helpful comments * includes a detailed index and phonetic transcription